Resistance of three implant-abutment interfaces to fatigue testing - Cleide Gisele Ribeiro; Maria Luiza Cabral Maia; Susanne S. Scherrer; Antonio Carlos Cardoso; H. W. Anselm Wiskott (University of São Paulo, 2011)
The design and retentive properties of implant-abutment connectors affect the mechanical resistance of implants. A number of studies have been carried out to compare the efficacy of connecting mechanisms between abutment and fixture. Objectives: The aims of this study were: 1) to compare 3 implant-abutment interfaces (external hexagon, internal hexagon and cone-in-cone) regarding the fatigue resistance of the prosthetic screw, 2) to evaluate the corresponding mode of failure, and 3) to compare the results of this study with data obtained in previous studies on Nobel Biocare and Straumann connectors. Materials and METHODS: In order to duplicate the alternating and multivectorial intraoral loading pattern, the specimens were submitted to the rotating cantilever beam test. The implants, abutments and restoration analogs were spun around their longitudinal axes while a perpendicular force was applied to the external end. The objective was to determine the force level at which 50% of the specimens survived 10(6) load cycles. The mean force levels at which 50% failed and the corresponding 95% confidence intervals were determined using the staircase procedure. RESULTS: The external hexagon interface presented better than the cone-in-cone and internal hexagon interfaces. There was no significant difference between the cone-in-cone and internal hex interfaces. Conclusion: Although internal connections present a more favorable design, this study did not show any advantage in terms of strength. The external hexagon connector used in this study yielded similar results to those obtained in a previous study with Nobel Biocare and Straumann systems. However, the internal connections (cone-in-cone and internal hexagon) were mechanically inferior compared to previous results.